Doing well-being: Self-reported activities are related to subjective well-being. - August Håkan Nilsson; Erik Hellryd; Oscar Kjell (PLoS ONE, 2022)
Activities and Subjective Well-Being (SWB) have been shown to be intricately related to each other. However, no research to date has shown whether individuals understand how their everyday activities relate to their SWB. Furthermore, the assessment of activities has been limited to predefined types of activities and/or closed-ended questions. In two studies, we examine the relationship between self-reported everyday activities and SWB, while allowing individuals to express their activities freely by allowing open-ended responses that were then analyzed with state-of-the-art (transformers-based) Natural Language Processing. In study 1 (N = 284), self-reports of Yesterday's Activities did not significantly relate to SWB, whereas activities reported as having the most impact on SWB in the past four weeks had small but significant correlations to most of the SWB scales (r = .14 -.23, p < .05). In Study 2 (N = 295), individuals showed strong agreement with each other about activities that they considered to increase or decrease SWB (AUC = .995). Words describing activities that increased SWB related to physically and cognitively active activities and social activities ("football", "meditation", "friends"), whereas words describing activities that decreased SWB were mainly activity features related to imbalance ("too", "much", "enough"). Individuals reported both activities and descriptive words that reflect their SWB, where the activity words had generally small but significant correlations to SWB (r =. 17 -.33, p < .05) and the descriptive words had generally strong correlations to SWB (r = .39-63, p < .001). We call this correlational gap the well-being/activity description gap and discuss possible explanations for the phenomenon.